STUDYING THE EFFECT OF WRAPPING THE STEEL BARS USING CARBON FIBER STRIPS ON THE BEHAVIOR OF REINFORCED CONCRETE BEAMS SUBJECT TO CYCLIC LOADING : - Jasem Mohamad , Halla (Journal of Applied Engineering Science, 2023)
The behavior of reinforced concrete beams subjected to cyclic loading was studied in this research to determine the impact of wrapping main reinforcing bars in carbon fibre (CFRB) strips. The objective of the present work included studying the impact of length and the number of layers of CFRB strips, that are used in wrapping main bars, on the overall response of reinforced concrete beams subjected to a cyclic load. Wrapping the reinforcing bars by Carbon fibre is a helpful substitute when there is no enough space to increase the quantity and size of these bars. For this purpose, five reinforced concrete beams were prepared and tested. One of these beams was a reference beam with unwrapped main reinforcement. Two beams have main steel bars wrapped along the mid third of the span with either single or two layers of CFRB. The main reinforcement for the remaining two beams was wrapped along their entire length with either single or double layers of CFRB. A nonlinear finite element analysis of the tested beams was carried out and the predicted results are compared with the experimental outcomes.  The results show that CFRB significantly and effectively contributes to increasing the flexural strength and overall behavior of the reinforced concrete beam at different rates depending on the length and number of CFRB layers that wrapped the steel bars.
Keywords: carbon fibre, cyclic load, layers, mode of failure, reinforced concrete, wrapping